Comment on "How green is blue hydrogen?". Issue 7 (29th March 2022) - Romano, Matteo C.; Antonini, Cristina; Bardow, André; Bertsch, Valentin; Brandon, Nigel P.; Brouwer, Jack; Campanari, Stefano; Crema, Luigi; Dodds, Paul E.; Gardarsdottir, Stefania; Gazzani, Matteo; Jan Kramer, Gert; et al.
Abstract: This paper is written in response to the paper "How green is blue hydrogen?" by R. W. Howarth and M. Z. Jacobson. It aims at highlighting and discussing the method and assumptions of that paper, and thereby providing a more balanced perspective on blue hydrogen, which is in line with current best available practices and future plant specifications aiming at low CO2 emissions. More specifically, in this paper, we show that: (i) the simplified method that Howarth and Jacobson used to compute the energy balance of blue hydrogen plants leads to significant overestimation of CO2 emissions and natural gas (NG) consumption and (ii) the assumed methane leakage rate is at the high end of the estimated emissions from current NG production in the United States and cannot be considered representative of all‐NG and blue hydrogen value chains globally. By starting from the detailed and rigorously calculated mass and energy balances of two blue hydrogen plants in the literature, we show the impact that methane leakage rate has on the equivalent CO2 emissions of blue hydrogen. On the basis of our analysis, we show that it is possible for blue hydrogen to have significantly lower equivalent CO2 emissions than the direct use of NG, provided that hydrogen production processes and CO2 capture technologies are implemented that ensure a high CO2 capture rate, preferably above 90%, and a low‐emission NG supply chain. Abstract : This paper is written in response to the paper "How green is blue hydrogen?" by R. W. Howarth and M. Z. Jacobson and aims at highlighting some flaws in the method and assumptions of that paper and at providing a more balanced perspective on blue hydrogen. By starting from the detailed and rigorously calculated mass and energy balances of two blue hydrogen plants in the literature, we show the impact that methane leakage rate has on the equivalent CO2 emissions of blue hydrogen. We conclude that for blue hydrogen to have a role in the transition to a renewable net‐zero economy, it is necessary to: (i) adopt hydrogen production processes and CO2 capture technologies ensuring high CO2 capture rate, possibly above 90%; (ii) develop a low‐emission natural gas supply chain, and (iii) adopt a life cycle approach based on reliable accounting of the methane leakage from the supply chain